Adolescência e violência escolar: das representações sociais às propostas de prevenção - Costa, Jaqueline Batista de Oliveira (2011)
This work presents the results of a research whose general objective was identifying the teenagers social representations about violence physical and nonphysical at school and their suggestions to the prevention/decreasing of this situation. Specifically we intended to know the teenagers social representations about the violence to school, of school and at school, as well as the possible relations that they establish among these categories; to verify if the teenagers distinguished, in their social representations, the several kinds of educational violence - physical and nonphysical and the possible relations that they established among them; to recognize the sources that contribute to the production and dissemination of teenagers social representations about violence; and know the purposes/suggestions that the teenagers present to prevention/decreasing of different kinds of school violence and, even, to what extent such strategies involve their participation. Accordingly, the theory of social representations - proposed by Serge Moscovivi (1978) and his followers - and also studies of authors that debate about violence and adolescence - subsidized the theoretic-methodologicals to the approach, interpretation and analysis of the object in study. A group of forty-eight teenagers made part of this research, from 6th to 9th year in Elementary School of two public schools in Presidente Prudente city, São Paulo state. It was used a questionnaire of characterizations of the subjects, submitted to the treatment of qualitative and quantitative analysis, and, as the main methodological procedure of data collection, we used the focus group technique. The collected material generated two corpora, called violence and purposes , that were submitted to a quantitative analysis, using the software ALCESTE (Analyse Lexicale par Contexte d un Ensemble de Segments de Texte), 4.7 version. The analyses showed that the teenagers, in their social representations, objectify the violence in familiar vocabulary, such as aggression, lack of respect, swearings, etc; they discriminated the different kinds, the frequency and the places where it happens; they demonstrated to distinguish the physical violence from the nonphysical and established relationships between them. The violence of school category aims, in the faculty s lack of commitment; in school negligence related to teachers absenteeism and the educators lack of authority or control, and, even, the omission of these ones when face the conflicts of violent nature. Nevertheless, they don t establish any relation between this kind of symbolic violence (of school) and the violence practiced at and against school. The sources that contribute to the production and dissemination of social representations of teenagers are: TV media, the own school, family, and friends. As purposes to the prevention/decreasing of educational violence, the teenagers suggest actions that involve repressive and punitive mechanisms; the interpersonal relations that establish themselves in school environment and the values construction, such as: mutual respect, the authority, the union, the dialogue, and the reconciliation